Intergovernmental collaboration challenges in Malawi’s immigration policy: insights from a collaborative governance model perspective - Kaisi, Sherrif Abobakar; Mohd Adnan, Normala; Aminudin, Rabi'Ah (Mashreq International for Books Sdn Bhd, 2024)
This paper examines intergovernmental collaboration on immigration policy in Malawi through the lens of the Collaborative Governance Model (Ansell & Gash, 2008). It focuses on the critical elements of institutional design, historical context, and facilitative leadership that influence collaborative efforts. The study highlights the importance of these factors in shaping effective governance among central and local government agencies and non-state actors. It argues that the unique institutional environments and contextual factors within Malawi significantly affect the dynamics of intergovernmental collaboration, thereby impacting immigration policy implementation and the development of effective relationships between governmental and non-state entities.